Analysis of The Factors Affecting Tourist Visits in Minahasa District - Rawung, Stanny Sicilia; Salindeho, Maya F. S.; Mantiri, Jeane (AIBPM Publisher, 2019)
The Long-Term Development Plan for 2010-2025 in the Minahasa district, establishes its area as one of the tourist destinations in North Sulawesi. In fact, the number of tourists visiting both domestic and foreign countries to this district is still far from what is expected, the objectives of this study are: (1) To find out more about the factors that influence tourist visits in Minahasa District (2) To find out more how is the potential of tourism competitiveness in Minahasa District compared to other Districts / Cities in North Sulawesi Province. This type of research is primary research using descriptive quantitative approach. The data sources used in this study are primary data obtained through survey data collection techniques. Secondary data used in this study are scientific publications issued by related parties, for example BPS and Minahasa District Tourism and Culture Office. The population in this study are all foreign tourists and domestic tourists visiting tourist attractions in Minahasa Regency. The researchers took samples accidentally from tourists who visiting the Kanonang Loving Hill and Moraya Tondano Fortress. 50 people each for each place. The total sample in this study was 100 tourists. The research questionnaire was prepared based on research variables, namely: the quality of human resources, promotion of tourism, tourism facilities. The data collected is analyzed using percentages which reflect the most dominant factors that affect to tourist visits in Minahasa District.